Species-specific differences in the behavior of male tsetse fly genitalia hidden in the female during copulation. Issue 1 (2nd January 2016) - Briceño, R.D.; Eberhard, W.G.; Chinea-Cano, E.; Wegrzynek, D.; Rolo, T. dos Santos
Abstract : A long-standing question in morphological evolution is why male genitalia tend to diverge more rapidly than other structures. One possible explanation is that male genitalia are under sexual selection to function as 'internal courtship devices'. Males of closely related species may provide divergent stimulation using different genital morphologies and behaviors. Testing this hypothesis has been difficult, however, because the presumed genital courtship behavior is often hidden from view inside the female, and because studies of how the male's genitalia interact with those of the female are nearly always limited to a single species in a given group, thus restricting opportunities for comparison of closely related species. We present new morphological and behavioral data for portions of the male genitalia that are hidden in the female during copulation in five species in the tsetse fly genus Glossina using data from dissections of pairs frozen in copula, artificially stimulated males, and from copulating pairs viewed with a new X-ray technique that allows events inside the female to be recorded in real time. These data almost certainly give only an incomplete view of this complex, previously hidden world. But even so they clearly reveal that, as predicted by sexual selection theory, the male genitalia of Glossina flies perform dramatic, stereotyped, rhythmic movements deep within the female's reproductive tract and in inward folds of her external surface, and that many of these movements probably differ among closely related species. Most of the movements are not explicable as means by which the male anchors himself more securely to the female; all are likely to result in stimulation of the female. A female Glossina can be stimulated tactilely at a given moment during copulation at up to 8–10 or more different sites on her body.